2019
DOI: 10.1044/2019_jslhr-s-19-0116
|View full text |Cite
|
Sign up to set email alerts
|

Going With the Flow: An Examination of Entrainment in Typically Developing Children

Abstract: Purpose Conversational entrainment is the tendency for individuals to modify their behavior to more closely converge with the behavior of their communication partner and is an important aspect of successful interaction. Evidence of entrainment in adults is robust, yet research regarding its development in children is sparse. Here, we investigate the emergence of entrainment skills in typically developing children. Method Data were collected from a total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 55 publications
(59 reference statements)
0
2
0
Order By: Relevance
“…Further studies have also found mixed evidence in terms of speech rate accommodation (Wynn et al, 2018(Wynn et al, , 2019. In these studies, the speech rate of typically developed adults converged towards the manipulated speech rate (slow/fast) of a female model speaker during a laboratory task.…”
Section: Speaking Ratementioning
confidence: 93%
“…Further studies have also found mixed evidence in terms of speech rate accommodation (Wynn et al, 2018(Wynn et al, , 2019. In these studies, the speech rate of typically developed adults converged towards the manipulated speech rate (slow/fast) of a female model speaker during a laboratory task.…”
Section: Speaking Ratementioning
confidence: 93%
“…Previous work from a developmental perspective has offered insight into the role and interaction of different factors and cognitive underpinnings at play in alignment in interaction at different levels, e.g., Dale and Spivey (2006); Fernández and Grimm (2014); Yurovsky et al (2016); Wynn et al (2019); Jiang et al (2022); Misiek and Fourtassi (2022); Fusaroli et al (2023); Kruyt et al (2023b). In the current study, part of a larger project exploring conversational dynamics in middle-childhood, we contribute to this developmental line of work, focusing on laughter mimicry and acoustic alignment in interaction.…”
Section: Alignment In Dialoguementioning
confidence: 99%
“…Filling the gap between these two life stages is of interest not only for improving our understanding of laughter mimicry across the lifespan, but also to enrich current theoretical models of alignment. Given the literature presented and the fact that various aspects of children's pragmatics in conversation, their acculturation (Mirski and Bickhard, 2021) and their socio-cognitive underpinnings are in continuous development in middle childhood (e.g., Lecce et al (2014);Wynn et al (2019); Osterhaus and Koerber (2021)), it is reasonable to hypothesise that laughter mimicry in middle-childhood might differ in comparison to adults.…”
Section: Laughter Mimicry In Child Developmentmentioning
confidence: 99%
“…These online adjustments during interactions—which often result in convergence on the complementary processes that define “good” conversation—can be understood as forms of adaptation. Conversational adaptation —which is conceptually related to research on accommodation, alignment, convergence, entrainment, coordination, synchrony, and social adaptation—is a process by which individuals alter their communicative behaviors in response to cues emitted by a conversation partner (Borrie et al, 2019; McNaughton & Redcay, 2020; Pickering & Garrod, 2006; Ratto et al, 2011; Wynn et al, 2019; Zampella et al, 2020). In this paper, we operationalize the term conversational adaptation to refer to adjustments in the amount of language (talkativeness) produced by participants across two different interaction contexts (i.e., with an interested vs. bored partner who talks more or less).…”
Section: Introductionmentioning
confidence: 99%